A macroscopic model on the dynamic behaviour of open cell foams. Issue 1 (17th December 2018) - Kirchhof, Stephan; Ams, Alfons
Abstract: Open cell foams are widely used in engineering which includes an application in areas, where vibration excitations can act on the structures. Therefore dynamical properties as eigenfrequencies and natural modes are of great interest. Here a modelling approach of the dynamic behaviour of open cell foams by macroscopic stochastic models will be discussed. Based on a 3D computed tomography scan of the foam, statistic and spectral analysis has been carried out to determine the parameters of the stochastic model. Additionally a vibration measurement has been done to provide eigenfrequencies, frequency transfer functions and natural modes of the real foam, which can be compared with the simulation results of the macroscopic model.